Microgeographic local adaptation and ecotype distributions: The role of selective processes on early life‐history traits in sympatric, ecologically divergent Symphonia populations. Issue 19 (17th September 2020) - Tysklind, Niklas; Etienne, Marie‐Pierre; Scotti‐Saintagne, Caroline; Tinaut, Alexandra; Casalis, Maxime; Troispoux, Valerie; Cazal, Saint‐Omer; Brousseau, Louise; Ferry, Bruno; Scotti, Ivan
Abstract: Trees are characterized by the large number of seeds they produce. Although most of those seeds will never germinate, plenty will. Of those which germinate, many die young, and eventually, only a minute fraction will grow to adult stage and reproduce. Is this just a random process? Do variations in germination and survival at very young stages rely on variations in adaptations to microgeographic heterogeneity? and do these processes matter at all in determining tree species distribution and abundance? We have studied these questions with the Neotropical Symphonia tree species. In the Guiana shield, Symphonia are represented by at least two sympatric taxa or ecotypes, Symphonia globulifera found almost exclusively in bottomlands, and a yet undescribed more generalist taxon/ecotype, Symphonia sp1 . A reciprocal transplantation experiment (510 seeds, 16 conditions) was set up and followed over the course of 6 years to evaluate the survival and performance of individuals from different ecotypes and provenances. Germination, survival, growth, and herbivory showed signs of local adaptation, with some combinations of ecotypes and provenances growing faster and surviving better in their own habitat or provenance region. S. globulifera was strongly penalized when planted outside its home habitat but showed the fastest growth rates when planted in its home habitat, suggesting it is a specialist of a high‐risk high‐gain strategy. Conversely, S. sp1 behaved as a generalist, performing well in a variety of environments. The differential performance of seeds and seedlings in the different habitats matches the known distribution of both ecotypes, indicating that environmental filtering at the very early stages can be a key determinant of tree species distributions, even at the microgeographic level and among very closely related taxa. Furthermore, such differential performance also contributes to explain, in part, the maintenance of the different Symphonia ecotypes living in intimate sympatry despite occasional gene flow. Abstract : A reciprocal transplantation experiment (510 seeds, 16 conditions) was setup and followed over the course of 6 years to evaluate the survival and performance of individuals from two different Symphonia ecotypes and provenances. The measured traits showed signs of local adaptation, with some combinations of ecotypes and provenances growing faster and surviving better in their own habitat or provenance region. The differential performance of seeds and seedlings in the different habitats matches the known distribution of both ecotypes, indicating that environmental filtering at the very early stages can be a key determinant of tree species distributions, even at the microgeographic level and among very closely related taxa.